2019
DOI: 10.1213/ane.0000000000003844
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Regulates Neural Stem Cell Proliferation and Differentiation via Calmodulin-Dependent Protein Kinase II/AMPK/ATF5 Signaling Axis

Abstract: BACKGROUND: Propofol can cause degeneration of developing brain cells and subsequent long-term learning or memory impairment. However, at the early stage of embryonic development, the molecular mechanism of propofol-induced inhibition in neural stem cells (NSCs) neurogenesis is still unclear. The aim of this study was to determine the role of propofol in NSCs neurogenesis and, more importantly, to explore the underlying mechanism. METHODS: First, a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…In this study, we found that sevoflurane exposure inhibited the self-renewal and differentiation of mouse embryotic NSCs. These findings were consistent with previous observations with other anesthetic drugs [18,25] and support the notion that exposure to anesthesia in early life can inhibit neurogenesis and cause neurological impairments [1,3]. Although the central nervous system, particularly for the brain in humans and rodents, usually undergoes continual Quantitative RT-PCR revealed that sevoflurane exposure increased miR-128-3p transcripts in NSCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that sevoflurane exposure inhibited the self-renewal and differentiation of mouse embryotic NSCs. These findings were consistent with previous observations with other anesthetic drugs [18,25] and support the notion that exposure to anesthesia in early life can inhibit neurogenesis and cause neurological impairments [1,3]. Although the central nervous system, particularly for the brain in humans and rodents, usually undergoes continual Quantitative RT-PCR revealed that sevoflurane exposure increased miR-128-3p transcripts in NSCs.…”
Section: Discussionsupporting
confidence: 92%
“…NSCs have potent self-renewal ability to form neurospheres and can differentiate into β-tubulin-III (Tuj1) + neurons, O4+ oligodendrocytes, and GFAP+ astrocytes [16,17]. Previous studies have shown that anesthesia, such as propofol, ketamine and isoflurane, can inhibit the self-renewal and differentiation of mouse NSCs [18,19]. Sevoflurane is commonly used in pediatric and obstetric anesthesia, and it is important to understand its potential neurotoxicity and mechanisms in NSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the data indicated that propofol would inhibit the proliferation of NSCs (Li et al, 2018;Liang et al, 2019). In our present study, propofol lengthened the G1 phase indicating a cell cycle arrest.…”
Section: Discussionsupporting
confidence: 70%
“…It has been suggested that propofol can disrupt neurogenesis by modulating apoptosis, proliferation, or the differentiation of neural stem cells (NSCs) (Zou et al, 2013). The potential mechanisms underlying these effects include regulation of the caspase-3 cascade (Karen et al, 2013), calmodulin-dependent protein kinase II, or microRNAs (miRNAs) (Hebert and De Strooper, 2009;Liang et al, 2019). However, the roles of miRNAs in the dysfunction of NSCs following propofol exposure are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin can induce the levels of DEP domain-containing mTORinteracting protein (DEPTOR), which intensifies binding to mTOR and exerts a suppressing effect on mTOR signaling in HCC (40). Previous research has shown that propofol suppresses the proliferation, differentiation, and migration of neural stem cells (NSCs), and these functions are partially mediated by the calmodulin-dependent protein kinase (CaMk) II/phosphorylation of serine at amino acid position 485 (pS485)/AMPK/activating transcription factor 5 (ATF5) signaling pathway (41). Importantly, the AMPK/ mTOR signaling pathway has been found to be activated in propofol-induced autophagosome accumulation in HeLa cells (42).…”
Section: Discussionmentioning
confidence: 99%